Courtly Carnality: Consuming Flesh in the Lai d'Ignaure. (2nd January 2023) - Revelle, Anthony
ABSTRACT: In the Lai d'Ignaure twelve ladies who share the same lover are tricked by their husbands into eating his heart and genitals, cooked as meat in a stew. When the jealous husbands declare that they have fulfilled the ladies' desire for flesh, the ladies counter with the claim that they were already replete with Ignaure's love, and they swear to die since they could never again have a meal of such worth. I argue that in Ignaure, as in other eaten heart stories, consuming the lover's flesh underscores a core carnality of courtly love, but here it also opens up an alternative model of love, focusing on consummated pleasure rather than desire, and celebrating the dissolution of bodily boundaries against a heteronormative distribution of gender positions. By claiming sexual satisfaction and forming a female homosocial collective based on their unapologetic sharing of a lover's flesh, the ladies invite a reconsideration of courtly love that values female pleasure over male desire, satiety over lack, and community over exclusivity. I demonstrate that circulations of flesh in Ignaure subvert the political, social, and gendered structures that define the court, for the lay calls on provocative ways of understanding—and enjoying—flesh.